Design and implementation of a CMOS Modulated Light Camera - Achamfuo-Yeboah, Samuel Osei (2012)
Modulated Light Cameras represent a breed of cameras designed specifically to capture intensity modulated light. This is because using coherent detection it is possible to lift a signal of interest out of the background noise and thus increase the precision of measurements.